Cane for the visually impaired - Santa Comba, Catarina Isabel Póvoa (2020)
The biggest struggle that visually impaired and blind people face on their daily basis is the ability to navigate outdoors independently and safely. In order to make the necessary deviations while maintaining the desired course, it is necessary that visually impaired travellers are capable of correctly detect possible hazards or obstacles. Even though the traditional mobility aids such as the guide dog and the white cane have proven to be valuable and effective tools in many mobility tasks, there are still situations where these means are not effective. Therefore, in the last decades, there has been a great investment in the research and development of electronic travel aids. At the University of Aveiro in the years of 2008 and 2009, were also developed two electronic canes which used ultrasounds to detect holes, drop-offs, and steps. However, in both prototypes, it was detected the presence of acoustic coupling of the signal between the emitter and receiver transducers which reduced drastically the efficiency of both devices. Thus, in this master thesis, it is proposed a solution to this issue using 3D printing also known as additive manufacturing. This technology has been growing exponentially in the last years and gaining prominence in several sectors such as industry, engineering, and medicine. In this specific case, it will be utilized to produced several prototypes of supports for the ultrasonic transducers in order to minimize the acoustic coupling.